Clinical manual of youth addictive disorders - Winters, Ken C.; Kaminer, Yifrah (Washington D.C. American Psychiatric Association, 2020)
Thoroughly updated and expanded, the book focuses on the clinical implications of beginning substance use and the pathways to substance use disorders (SUDs) and coexisting disorders among adolescents and college-age emerging adults (ages 12--25 years). This new manual not only captures the advances made in the youth substance use and SUD domains covered in the previous manual, but also includes new and critically important topics that have emerged.
Keywords: Psicología clínica; Adicción; Drogas; Adolescentes -- Psicología; Toxicomanía -- Tratamiento